Rasionalitas Terapi Antibiotik Empiris pada Pasien Geriatri dengan Community-Acquired Pneumonia di RS Mardi Rahayu - Kristi Noviana Aryadi; Zullies Ikawati; Probosuseno Probosuseno (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Community-acquired Pneumonia (CAP) is an acute infectious disease that affects the tissues (lungs) precisely in the alveoli acquired outside the hospital. The incidence of pneumonia increases with age due to changes in physiologic and immunological status associated with aging and the presence of comorbidities in old age. Pneumonia is the biggest infectious disease in Mardi Rahayu Hospital from 2020 to 2022. Inappropriate selection of empiric antibiotics causes antibiotic resistance and their prolonged use can increase the length of stay so that the cost of treatment increases. Rationale analysis of the use of specific empiric antibiotics in geriatric patients with CAP at Mardi Rahayu Hospital has never been carried out. This study aims to determine the rationality of empirical antibiotic therapy in geriatric patients with CAP. This study used a descriptive and analytic observational design with a cross-sectional method. Analysis of the rationality of empirical antibiotic therapy using the Gyssens method. The results showed that the number of geriatric patients diagnosed with CAP who were hospitalized at Mardi Rahayu Hospital from January to December 2022 who met the inclusion criteria was 139 patients with a total of 158 antibiotic regimens. The results of the rationality analysis showed that as many as 95 antibiotic regimens (60.1%) were included in the 0 (zero) category, which means rational use of antibiotics. Irrational use of antibiotics occurred in 63 regimens in category IV-A as 40 cases (25.3%), IV-B as 9 cases (5.7%), IV-C as 2 cases (1.2%), III- A as 9 cases (5.7%), III-B as 20 cases (12.6%) and II-A as 2 cases (1.2%).